Welfare Of Islamic People Based On The Concept Of Madani Society Life - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2025)
As Muslims who want to apply life according to the concept of civil society, we should apply manners and behavior as exemplified by Rasulullah SAW during his leadership in the city of Medina, because by implementing life according to this concept, we will achieve a prosperous life. Then, in living like a Muslim, of course we will not be separated from interactions related to the economy. So in this era full of modernity and globalization, we should continue to apply the Islamic economic system in accordance with Sharia. Likewise, it is our obligation as Muslims who live with our other Muslim brothers, to purify the wealth we own, as well as to help each other, we should pay zakat and make waqaf. With this, mahabbah or love will arise between fellow Muslims.